HPMC (hydroxypropyl methylcellulose) as a fat replacer improves the physical properties of low‐fat tofu. (8th March 2017) - Shin, Woo‐Kyoung; Wicker, Louise; Kim, Yookyung
Abstract: BACKGROUND: The effect of the addition of hydroxypropyl methylcellulose (HPMC) on the textural properties of low‐fat tofu was investigated. Three fat levels (240, 100 and 30 g kg −1 ) were used to make tofu, which were identified as C (full‐fat tofu), L1 and L2. HPMC (5 g kg −1 ) was added to soymilk to prepare control and low‐fat tofu, designated as CH, L1H and L2H. RESULTS: Soymilk with a lower fat level had a lower viscosity: 143 (C), 100 (L1) and 42 (L2) cP. The addition of HPMC increased the viscosity of all types of soymilk, particularly in L2H (107 cP). With fat reduction, tofu syneresis increased from 19% (C) to 29% (L2), although syneresis of L2H recovered to 19%, which is similar to high‐fat control tofu. Decreased fat resulted in a lower firmness in L2 (0.67 N) compared to control (0.78 N). Firmness increased to 1.08 N in L2H tofu, whereas the firmness of CH tofu was 0.63 N. All types of tofu showed a denser, well‐connected and cross‐linking structure when HPMC was added, especially in L2H tofu. CONCLUSION: HPMC improved the texture of the low‐fat tofu by creating a harder texture and reducing syneresis. HPMC is an effective fat replacer for lower fat soymilk. © 2017 Society of Chemical Industry